Outdoor stereo camera system for the generation of real-world benchmark data sets - Meister, Stephan Nicolas Robert; Jähne, Bernd; Kondermann, Daniel (Optical engineering, 2012)
We describe a high-performance stereo camera system to capture image sequences with high temporal and spatial resolution for the evaluation of various image processing tasks. The system was primarily designed for complex outdoor and traffic scenes that frequently occur in the automotive industry, but is also suited for other applications. For this task the system is equipped with a very accurate inertial measurement unit and global positioning system, which provides exact camera movement and position data. The system is already in active use and has produced several terabytes of challenging image sequences which are partly available for download.
Gesehen am 10.01.2019